Trends, Issues, Opportunities, and Challenges in the Digitalization Era: Utilizing Educational Technology to Support the Implementation of the Independent Curriculum at SMA Negeri 8 Tasikmalaya City - Rahayu, Ayu Puji; Sonari, Heny; Robby, Asa; Rahmawati, Ine (Indonesian Journal of Community Empowerment (IJCE), 2022)
This community service activity was conducted to analyze trends, issues, opportunities, and challenges in the utilization of educational technology to support the implementation of the Merdeka Curriculum at SMA Negeri 8 Tasikmalaya. Using a descriptive qualitative approach, data were collected through training, group discussions, and interviews with teachers to gain insights into their readiness and practices in applying digital learning tools. The results revealed that teachers demonstrated strong enthusiasm and awareness of the importance of technology for enhancing project-based learning, collaboration, and independent learning in line with the philosophy of the Merdeka Curriculum. Teachers began integrating various platforms such as Learning Management Systems (LMS), Google Classroom, Canva, and Quizizz, and they also recognized the potential of advanced tools such as Augmented Reality (AR) and Artificial Intelligence (AI) in increasing student engagement. Nevertheless, several issues arose, including limited digital literacy among teachers, unequal access to devices among students, and inadequate internet infrastructure. These challenges often hinder the optimal use of technology in classrooms. On the other hand, opportunities were identified in the form of teacher capacity building, interactive learning design, and increased student motivation through technology-based media. The findings of this program highlight that the successful implementation of the Merdeka Curriculum requires continuous mentoring, collaborative practices among teachers, and strong institutional support in providing adequate facilities and digital infrastructure.